PENGARUH GAYA KEPEMIMPINAN, PROFESIONALISME, DAN KOMPLEKSITAS TUGAS TERHADAP KINERJA AUDITOR - Lasefie Zahiya Pertiwi (2021)
This study aims to determine the effect of leadership style, professionalism, and task complexity on auditor performance. This study uses auditors at several Public Accounting Firms in the South Jakarta area as samples. The sampling technique used is simple random sampling. The sample in this study were 90 respondents from 19 Public Accounting Firms (KAP) in the South Jakarta area. The data used in this study is primary data, namely the provision of questionnaires to KAP. Testing the hypothesis of this study using Multiple Linear Regression Analysis using Statistics Program and Service Solution (SPSS) version 25 and a significance level of 5%. The results of the study that (1) leadership style has a significant positive effect on auditor performance, (2) professionalism has a significant positive effect on auditor performance, (3) task complexity has a significant positive effect on auditor performance.